Teoretyczne problemy controllingu - definicja - Foremna-Pilarska, Monika (Theoretical Problems of Controlling - Definition, 2007)
Despite the passage of years and the functioning of controlling in Poland, there is not still one definition. Controlling has in practice a lot of variants and it has a lot of tasks in an enterprise. Such a state can contribute to the lack of one a precise definition of controlling which would to be in force both in theory and practice. The article has an aim to review the multitude ways of controlling definition interpretation and to propose one of them which is coherent and which joins both practical and theoretical aspects of controlling.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 154-162